Hematoma vulvo-vaginal: exceptional etiology of obstetrical near miss - Dorland, Ranjandriarison Tafitarilova; Rabarikoto, Hary Fanambinantsoa; Raelison, Jasper Grant; Randriambololona, Domoina Malala Aurelia; Rajaonera, Tovohery Andriambelo; Andrianampanalinarivo, Hery (International Journal of Research in Medical Sciences, 2021)
Postpartum hematoma, rare among several causes of postpartum hemorrhage, is exceptionally reported in the etiologies of obstetrical near miss. The authors reported a case of large vulvo-vaginal hematoma after home delivery in a 26 year old patient of Franco-Indian descent. The patient was admitted in a state of hemorrhagic shock combined with an impregnable blood pressure, a significant skin-muquauses pallor and conscience disorder. Its management required a good coordination between the anesthesia team and the obstetrical team as it was based on the hemostasis results after surgical evacuation of the hematoma for more than 1000 ml blood and corrections of blood crass disorders.